Perancangan Alat Pengukur Tinggi Badan dan Berat Badan untuk Penentuan Kondisi Gizi Bayi - Ubaidillah, Achmad; Joni, Koko; Afif, Nasrul; Kholida, S. Ida (Rekayasa, 2024)
Nutrition is very important for the healthy and normal growth of babies. Determination of infant nutrition is usually calculated from two parameters, namely the baby's height and weight. Both data are then calculated manually to determine the nutritional condition of the baby. The process is considered relatively inefficient. Research is very important to overcome this problem, which will be made a measuring device for height and weight to determine the nutritional condition of babies automatically. This research uses a camera to measure height and a strain gauge sensor to measure weight. Both tools are integrated in a toddler box. The measurement data is then processed by the ATmega16 microcontroller and sent to a PC/laptop for evaluation, storage and appearance of the toddler's condition automatically on the database server. With this research, it is hoped that parents can monitor their baby's nutrition at any time easily and quickly. Based on experiments that have been carried out, measurement of height and weight for determining the nutritional status of infants using the canny detection method, has an average accuracy of 97.32%.